СВЧ полевые транзисторы средней мощности миллиметрового диапазона длин волн - Ivashchuk, A. V.; Bosy, V. I.; Kovalchuk, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper presents the results of optimization of the design and fabrication technology of microwave field-effect transistors of medium power with an operating frequency in the range of 18–36 GHz on GaAs epitaxial structures. The output power of the transistors is about 100 mW at 1 dB compression, the noise figure does not exceed 3.0 dB, and the power gain is at least 4 and 7 dB at frequencies of 36 and 18 GHz, respectively. The design of measuring devices and the methodology for studying these parameters in the short centimeter and millimeter wavelength ranges are described.